Inside network perimeter security - Northcutt, Stephen (Sams Pub., 2005)
Security professionals and administrators now have access to one of the most valuable resources for learning best practices for network perimeter security. Inside Network Perimeter Security, Second Edition is your guide to preventing network intrusions and defending against any intrusions that do manage to slip through your perimeter. This acclaimed resource has been updated to reflect changes in the security landscape, both in terms of vulnerabilities and defensive tools. Coverage also includes intrusion prevention systems and wireless security. You will work your way through fortifying the perimeter, designing a secure network, and maintaining and monitoring the security of the network. Additionally, discussion of tools such as firewalls, virtual private networks, routers and intrusion detection systems make Inside Network Perimeter Security, Second Edition a valuable resource for both security professionals and GIAC Certified Firewall Analyst certification exam candidates.